SÓ POR CURTIÇÃO: UMA ETNOGRAFIA SOBRE O USO DO VAPE POR JOVENS EM CAMPO GRANDE - MS - Dihego Flores Espíndola (2023)
This research aims to describe and develop an ethnography about social interactions, and analyze how linked they are to the use of electronic smoking devices (e-cigarettes) by young people, which is an increasingly recurrent behavior at events, parties, colleges and bars in the city of Campo Grande/MS, especially among undergraduate students and those who are in pre-university preparation courses. With this study, I seek to understand how the ritual is established, and how it encourages symbolic actions, behaviors and affections among young people, drawing an identity distinction but, at the same time, leading to the construction and disintegration of the social groups researched. Therefore, fieldwork was carried out, with lengthy descriptions and accounts given by people from different walks of life, with gender and age differences, from middle to upper class. I based the anthropological analysis on Erving Goffman and his concepts of “Social Interaction”, “Masks falling off” and “Symbolic Action”, as well as on Stuart Hall’s notion of “Identity”. I infer, in my final considerations, that the social interaction promoted by parties and by the excessive use of e-cigarettes provoques a plethora of ritualistic processes and a constant search for self-affirmation of their social identity. Thus, the ritual provides not only the development of social interaction, but also the moment of the fallen mask, when, after the diagnosis of lung diseases, such individuals are abandoned by their groups and no longer make efforts to belong there. KEYWORDS: Social Interaction; Identity; Fallen Mask off; Vape; E-cigarettes;